2013
DOI: 10.1111/geb.12133
|View full text |Cite
|
Sign up to set email alerts
|

Global dependence of field‐observed leaf area index in woody species on climate: a systematic review

Abstract: Aim Leaf area index (LAI) is one of the key variables related to carbon, water and nutrient cycles in terrestrial ecosystems, but its global distribution patterns remain poorly understood. We evaluated the dependence of LAI on mean annual temperature (MAT) and wetness index (WI; a ratio of annual precipitation to potential evapotranspiration) for three plant functional types (PFTs: deciduous broadleaf, DB; evergreen conifer, EC; evergreen broadleaf, EB) at the global scale.Location Global. MethodsWe developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 51 publications
8
75
4
Order By: Relevance
“…We emphasize that we have used a consistent method to derive our canopy structure estimates for each plot. This is an important difference to previous analyses (Iio et al 2014), because optical instruments can produce large discrepancies between canopy structure estimates in particular for lowheight canopies and canopies with senescent vegetation and high spatial heterogeneity (Garrigues et al 2008). …”
Section: Forest Canopies and Climatementioning
confidence: 87%
See 3 more Smart Citations
“…We emphasize that we have used a consistent method to derive our canopy structure estimates for each plot. This is an important difference to previous analyses (Iio et al 2014), because optical instruments can produce large discrepancies between canopy structure estimates in particular for lowheight canopies and canopies with senescent vegetation and high spatial heterogeneity (Garrigues et al 2008). …”
Section: Forest Canopies and Climatementioning
confidence: 87%
“…Previous studies focussing on temperate natural forests and forest plantations (Iio et al 2014) and tropical forests in East Africa (Pfeifer et al 2014) have found a decline in canopy LAI in regions with very high levels of rainfall and water availability. This is in line with studies showing a decline in NPP of humid tropical forests under high rainfall regimes, with NPP peaking at around 2500 mm mean annual rainfall, with subsequent declines linked to decreased radiation inputs (high cloud cover), increased nutrient leaching, or reduced soil oxygen Fig.…”
Section: Forest Canopies and Climatementioning
confidence: 99%
See 2 more Smart Citations
“…Leaf area index (LAI) is an important variable for understanding architecture and biological processes in trees [1], designing silvicultural treatments [2], for landscape-level ecosystem process models [3], or global forest functions [4]. LAI has been defined as the sum of projected (one-sided), or all-sided leaf areas, for all trees in a given area divided by the land surface area the trees cover [5].…”
Section: Introductionmentioning
confidence: 99%